Effect of SiC whisker on properties of SiBCN based ceramic composites - WEI Wei; LIU Wei; LI Qi; CAO Lamei (Cailiao gongcheng, 2023)
SiC whisker was added into SiBCN ceramics obtained by pyrolysis of polyborosilazane (PSNB) by ultrasonic combined with ball milling. The effects of different mass fractions SiC whisker on the density, hardness, bending strength and microstructure of SiBCN ceramic matrix composites were studied. The results show that with the mass fraction of SiC whisker increasing from 0% to 25%, the density of the composite is first decreased and finally increased, the porosity is gradually increased, the hardness is gradually decreased, and the bending strength is first increased, then decreased and finally increased; It was found that the three-point bending strength of SiCw/SiBCN composite with 5% SiC whisker can reach 191 MPa, which is 218% higher than that of pure SiBCN matrix without whisker (60 MPa). XRD analysis shows that the introduction of whiskers has little effect on the phase composition of sintered composites; by observing the micro morphology of the fracture surface of the materials, it was found that the existence modes of whiskers in the matrix mainly include bridging and agglomeration bridging. Bridging whiskers are conducive to strengthening the material, while agglomerated whiskers will form pores in the matrix, so as to reduce the strength of the material.